Тhe features of severe community acquired pneumonia. - I. V. Avramenko (Medičnì Perspektivi)
Based on data from a prospective analysis for the year of observation, the article presents information about the features of severe community acquired pneumonia in patients who were hospitalized at the department of pulmonology (or therapy), as well as department of  the intensive care from three teaching hospitals in Dnepropetrovsk, namely  "Dnipropetrovsk City Hospital №6», "Dnipropetrovsk City Hospital №2», "Dnipropetrovsk City Hospital №16», which are the clinical onesof "Dnepropetrovsk Medical Academy of the Ministry of Health Ukraine". Dependence of the severity of the condition shownon duration of illness before admission, features of season character of disease. The effect of breathing exercises on the course of the disease. The results can be the basis for a more personal approach to the development of diagnostic and therapeutic programs for patients with severe community-acquired pneumonia.